ETHICS OF ARTIFICIAL INTELLIGENCE IN CREATIVE EXPRESSION AND CULTURAL PRODUCTION - B , Saraswati; R, Harshini; B, Gayathri; S, Saravana Kumar; Ganapathy, Bhavani; Arumugam, Mahendran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Artificial Intelligence (AI) has become a strong technology of creative expression and culture production that enables the introduction of new forms of artistic imagination and the creation of content using digital tools. Machine learning systems, generative algorithms, and natural language processing systems are tools of AI-inspired systems commonly used in visual arts, music composition, literature, film production, and the digital media. Though the technologies raise the potentiality of creative work and make the process more efficient, there are also negative ethical aspects about authorship, copyrights, culture representation, algorithms bias, and transparency of the products created by AI. This study aims at understanding the ethics of AI in the creative industry, and how the theories of ethics currently used address these issues. The paper discusses the major implementation of AI ethics principles that are being established by the international organizations such as OECD, UNESCO and IEEE, and reflects on how these principles can be applied to the sphere of creative and cultural practices. On the platform of comparison and contrast, the deficiency of the currently employed frameworks can be identified in relation to the visibility of the matters of artistic ownership, cultural sensitivity, and human-AI cooperation. To address these gaps, this paper proposes the conceptual Ethical AI Framework of Creative Expression which includes ethical considerations, responsible AI development practices, approaches to governance and continuous monitoring approaches. The proposed model is oriented on openness, equality, responsibility, the protection of the right to creators, and the consideration of the cultural diversity in the benefit of human beings and AI mechanisms working together in creativity. The analysis proves that the introduction of field-specific standards of ethics is the key to responsible and sustainable use of AI technologies in the creative field. Having ethics in leadership and technology innovation, the proposed framework provides the guidelines of creating trustworthy AI systems to increase creativity and safeguard culture and artistic rights.